Chromogranin B (CHGB) is dimorphic and responsible for dominant anion channels delivered to cell surface via regulated secretion - Yadav, Gaya P.; Wang, Haiyuan; Ouwendijk, Joke; Cross, Stephen; Wang, Qiaochu; Qin, Feng; Verkade, Paul; Zhu, Michael X.; Jiang, Qiu-Xing (Frontiers in Molecular Neuroscience, 2023)
Regulated secretion is conserved in all eukaryotes. In vertebrates granin family proteins function in all key steps of regulated secretion. Phase separation and amyloid-based storage of proteins and small molecules in secretory granules require ion homeostasis to maintain their steady states, and thus need ion conductances in granule membranes. But granular ion channels are still elusive. Here we show that granule exocytosis in neuroendocrine cells delivers to cell surface dominant anion channels, to which chromogranin B (CHGB) is critical. Biochemical fractionation shows that native CHGB distributes nearly equally in soluble and membrane-bound forms, and both reconstitute highly selective anion channels in membrane. Confocal imaging resolves granular membrane components including proton pumps and CHGB in puncta on the cell surface after stimulated exocytosis. High pressure freezing immuno-EM reveals a major fraction of CHGB at granule membranes in rat pancreatic β-cells. A cryo-EM structure of bCHGB dimer of a nominal 3.5 Å resolution delineates a central pore with end openings, physically sufficient for membrane-spanning and large single channel conductance. Together our data support that CHGB-containing (CHGB+) channels are characteristic of regulated secretion, and function in granule ion homeostasis near the plasma membrane or possibly in other intracellular processes.